DETERMINAN PENGGUNAAN ALAT KONTRASEPSI DALAM RAHIM (AKDR) PADA WANITA PASANGAN USIA SUBUR - Okvitasari, Yenny; Triswanti, Triswanti; Putra, Bayu Pratama; Ramli, Kamrianti; Sriwahyuni, Sriwahyuni (Ensiklopedia of Journal, 2024)
Based on an initial survey conducted at the Garuda Health Center regarding the implementation of the Family Planning program, it was found that the number of registered Fertile Age Couples (PUS) was 12,603 people, but only 244 people were actively using Intrauterine Contraceptives (IUD). This study aims to identify factors that influence the use of IUDs in women of childbearing age. The research method used was quantitative analytic observational with case control study design. Sampling was conducted using systematic random sampling technique, with a ratio of 1:1 between cases and controls, each consisting of 148 people. Data were collected through a research questionnaire and analyzed univariately and bivariately. The results showed an association between income (p value 0.028; OR 2.016), husband support (p value 0.033; OR 1.712), and family planning history (p value 0.038; OR 1.057). It is recommended for the Garuda Health Center to be more active in providing health information to increase the knowledge and awareness of married couples about the use of IUDs.Keywords: IUD, Income, Husband's Support, Family Planning History